Sosialisasi Marketing Mix Pada Home Industry Sambal Pecel Dusun Putat 1 Kabupaten Gunung Kidul - Kartinasari Ayuhikmatin Sekarjati; Angger Bagus Prasetiyo (Jurnal Berdaya Mandiri, 2021)
Developments that occur in companies and entrepreneurs in the marketing department require and entrepreneurs to think creatively in order to be able to survive in this intense competition. Community service counseling was carried out regarding the socialization of the marketing mix to the people of Putat 1 Hamlet, Putat Hamlet, Gunung Kidul. The purpose of conducting this marketing mix outreach activity is to answer the latest problems of the people of Putat 1 Hamlet in developing their entrepreneurship. To improve the economy of the people of Putat 1 Hamlet, develop the potential for processed products, namely the chili pecel product. The 7P marketing mix method is used as a reference in developing the sambal pecel entrepreneurship, especially in the marketing section by the people of Putat Village 1.The results obtained from this outreach activity are the increase in knowledge Putat 1 Hamlet community regarding the marketing of the chili pecel product.